Ethno- medicinal studies on barks of some medicinal plants in Marathwada (M. S.), India –I - A, Gitte T; Kare, M A; Deshmukh, A M (Recent Research in Science and Technology, 2012)
The Present study provides information regarding the traditional uses of barks of some medicinal plants in Marathwada. Comprehensive ethno medicinal survey conducted in different community blocks of Marathwada region during 2009-2012. It revealed that many plant parts are used as traditional drugs for the treatment of various ailments by the local people. It was also observed that the barks of many plants have high medicinal properties and are used as traditional medicines. Some important such plants are Acacia nilotica (L.) Del. subsp.indica (Benth.) Brenan, Adansonia digitata L., Aegle marmelos (L.) Corr., Ailanthus excelsa Roxb., Albizia lebbeck (L.) Willd., Alstonia scholaris (L.) R.Br., Azadirachta indica A.Juss., Bauhinia racemosa Lamk. Bauhinia variegata L., Butea monosperma (Lamk.) Taub., Crateva adansonii Dc. subsp.odora (Buch.Ham.)Jacobs., Diospyros melanoxylon Roxb., Erythrina suberosa Roxb., and Holoptelea integrifolia (Roxb.) Planch.